Olive wastewater bioremediation using a rotating biological contactor (RBC) - Tapon Njamo, Julien Serge (Cape Peninsula University of Technology, 2012)
The expansion of the South African olive processing industry has brought an increased threat to the environment. More production activities lead to more wastewater generation that requires more costly treatment. Regulatory bodies concerned with the release of effluents into the environment are imposing evermore-restrictive guidelines. With this information in mind, the South African olive industry is facing a significant challenge of maintaining economic competitiveness while becoming more environmentally benign. To begin addressing this challenge, the olive processing industry must develop and implement new, more effective, tailored treatment technologies to remediate olive wastewater prior to its release into the environment. In this study, the use of indigenous olive wastewater biofilms in combination with a rotating biological contactor (RBC) was investigated for possible bioremediation purposes. The development of microbial biofilms resulted in the breakdown of the hazardous chemical compounds present in the olive wastewater, i.e. reducing the chemical oxygen demand (COD) and polyphenol content. Results showed that indigenous microorganisms within table olive and olive mill wastewater have a strong tendency to form biofilms. Furthermore, when these biofilms are applied to a small-scale RBC system, significant lower levels of both COD (on average 55% for table olive wastewater (TOWW) and 46% for olive mill wastewater (OMWW) and total phenol (on average 51% for TOWW and 39% for OMWW) were obtained. Results from shocking the biofilms with chemicals routinely used during olive processing indicates that most have a negative effect on the biofilm population, but that the biofilms are able to survive and recover in a relatively short time. This study confirms the potential application of indigenous biofilms found in olive wastewater streams for future bioremediation technologies that form the basis for the development of an eco-friendly, easy-to-manage, low cost technologies specifically designed for the small South African olive processing industry.
Thesis (MTech (Food Technology))--Cape Peninsula University of Technology, 2012.
Keywords: Olive -- Processing; Olive oil industry -- Waste disposal; Bioremediation; Olive mill wastewater